PELAKSANAAN PENGAWASAN PENEMPATAN PAPAN REKLAME DI KOTA PEKANBARU - ANGI RISKY PANDIANGAN; SUJIANTO " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Abstrac : Monitoring the implementation of the placement of billboards in the city of Pekanbaru. This study aimed to determine how the implementation of surveillance placement billboard in the city of Pekanbaru. Qualitative descriptive study where data acquisition is done by snowball technique. Monitoring the implementation of the research results show the placement of billboards in the city of Pekanbaru is not going up, it is proved in ideally with no ad placement.Keywords: Billboards, Placement, Controlling